Remedy in the case of a faulty declaration of nullity of a definitive sentence Canon 1626 - Daniel, William L. 1980- (2011)
"Our tribunal issued a negative decision in a cause of marriage nullity, and the petitioner appealed it to the ordinary appellate tribunal. The appellate tribunal declared the sentence irremediably null due to the absolute incompetence of the judge and due to a defect in the power of judging (c. 1620, 1°-2°). This conclusion was reached due to the invalid appointment of an associate judge, who had initially been assigned as defender of the bond in the case but had been substituted by another. We noticed that the appellate tribunal did not cite the promoter of justice before declaring the sentence null. Was this sentence legitimately declared null? If not, what can we do about it?"
Keywords: Katholische Kirche; Prozessrecht; Eheprozess; Urteil; Nichtigkeit; Nichtigkeitsbeschwerde; Rechtsschutz; Rechtsmittel; Ehenichtigkeitsverfahren